A comparative study on the effect of clay loading under normal and auto thermal extrusion to the morphology structure and thermal stability of nylon 6 nanocomposites - Faridah, Mohd Nor (2013)
The main purpose of this thesis is to study the influence of auto thermal extrusion on the thermal stability and morphology of fabricated PA6/C20A nanocomposite.The organically modified layered silicates type Cloisite 20A (the montmorillonite modified with a quaternary ammonium salt) and Polyamide 6(PA6) were used in this research. Fabricated PA6/C20A nanocomposite was prepared by using an auto thermal melt extrusion.The screw speed of twin screw extruder was maintained at constant value of 200 rpm,the clay loadings C20A were varied between 1-5 wt% respectively. The morphological properties were characterized by using both X-Ray Diffraction analysis(XRD)and Scanning Electron Microscopy(SEM),while the thermal stability of obtained PA6/C206 nanocomposite was studied by using thermo gravimetric analysis (TGA).The dispersion and distribution of nanoclays platelets within the polymer matrix,a clay contents show a better role in dictating the quality of extruded PA6/C20A nanocomposite than the auto thermal or conventional setting extruder itself based on the evidently formation number of agglomerated clay.The degradation T onset of PA6/C20A nanocomposite was found to be shifted to the larger value under an auto thermal extrusion.As a conclusion,auto thermal extrusion is suggested as an alternative approach for energy cost reduction and efficiency application in the industry.